Life cycle assessment (LCA) of wood plastic composite (WPC): Identifying end-of-life option / Zakiah Hani Ab Rashid - Ab Rashid, Zakiah Hani (2019)
Wastes and scraps from wood based and plastic industry can contribute to environmental harm if no appropriate handling methods are taken. Combinations of both wood and plastic wastes are able to produce wood plastic composite. The objective of this research was to observe the LCA of the WPC and to determine the physical and mechanical properties of WPC after recycle process. Three different filler loadings (50%, 70% and 90%) were used. Blending of polypropylene with sawdust took place in the dispersion mixer for I hour at 180 °C before hot pressed and old pressed. Next, testing on bending, tensile, water absorption and thickness swelling were done. Results shown that there was a significant effect of different amount of loadings and recycle of filler loadings on the wood plastic composite. 70% of polypropylene with 30% of wood filler showed the highest percentage mechanical properties for tensile and bending MOR. While for the recycling process, first recycle showed the highest strength of tensile and bending. Thermoplastic composite boards were then tested for tensile, bending, water absorption are according to ASTM standard